Code Switching on Students’ Group Presentation in EFL Classroom - Harmilawati Harmilawati (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The study aimed to find out the functions of code switching used by the lecturer and the students during group presentation, and the lecturer and the students’ perception toward the use of code switching in EFL classroom during group presentation. This study is a qualitative research design. The subjects of the study were an English lecturer and three students in second semester of STKIP Muhammadiyah Bone, which were taken through convenience sampling technique. The data of this study were collected by employing classroom observation and interview. The data obtained were analyzed descriptively by using three steps, namely reducing, describing, and classifying. The result of the research showed that the lecturer employed code switching in EFL classroom during the students’ group presentation for some functions, namely to emphasize the important point, to reinforce a request, to ease of expression, to change of attitude relationship, checking for students’ understanding, lapses, self-correction, and speech connective. To emphasize the important point and reinforce a request became most frequently used by the lecturer. There were five functions of code switching used by the students during group presentation, namely to emphasize the important point, to suit the domain knowledge, to reinforce a request, to change of attitude relationship, and to self-correction. To suit the domain knowledge became the most frequently used by the students. The lecturer and the students’ perception towards the use of code switching in EFL classroom during group presentation were mostly positive. The lecturer and the students need code switching in teaching and learning English because it can make them easy to understand and comprehend from the material given. Code switching also effective in enlarging the students’ vocabulary, helped them to learn English, made them be more active in classroom interaction and influenced their fluency in speaking English.